ChemInform Abstract: Baking ′Crumbly′ Carbon Nitrides with Improved Photocatalytic Properties Using Ammonium Chloride. Issue 14 (March 2016) - Savateev, Aleksandr; Chen, Zu Peng; Dontsova, Dariya
Abstract: NH4 Cl is used as a green, unreactive, and reusable template to produce heptazine‐based graphitic C3 N4 with surface areas of up to 30 m 2 /g by pyrolysis of a reaction mixture containing NH2 CN and NH4 Cl in ratios of 1:2, 1:5, and 1:10 under flowing N2 (550 °C, 4 h).